Reading August Strindberg's Miss Julie: A Quest for Agency (Sudurpaschim Spectrum, 2024)
This article seeks female agency amid a dichotomous portrayal of the male-female in the characters in the drama, Miss Julie with the feminist lens. It finds a relationship between the two is like controller and controlled that leads the work to critiquing pervasive patriarchal influence in the contemporary culture. It draws on critical and theoretical insights from Antinio Gramci, Hélène Cixous and other critical viewpoints from scholars. These considerations are central to critiquing the male dominance by highlighting female will to search for their agency and space of equality through August Strindberg's play Miss Julie that serves as a vivid picture of patriarchal control by illustrating the downfall of the protagonist, Julie, who relinquishes her privileged status through her affair with her father's valet, Jean. Julie is portrayed as a "half woman," grappling with psychological instability and a lack of autonomy, in stark contrast to Jean, who retains his moral superiority and emerges unscathed. The narrative underscores a gendered double standard were women like Julie face condemnation for their desires and choices, while men like Jean evade responsibility. Although Strindberg attributes Julie's tragic fate to her personal shortcomings and societal pressures, he neglects to acknowledge the pervasive gender biases that dictate her life. This article emphasizes how Miss Julie upholds hegemonic patriarchal norms that devalue women's experiences and reinforces the stereotypical image of women as less valuable within the confines of patriarchal ideology.